Study for estimating solar radiation in Elazig using geographical and meteorological data - Türk Togrul, Inci; Onat, Emin (Elsevier Science Ltd, 1999)
In this study, the effect of geographical and meteorological parameters on the monthly mean global solar radiation in Elazig was investigated. A multiple linear regression was applied to six geographical and meteorological data sets, which were monthly mean extraterrestrial radiation, the ratio of 'bright sunshine hours to daylength', ambient and soil temperatures, humidity and sine of declination angle. The global solar radiation estimated from the models was compared with the values measured by the Kipp-Zonen pyranometer between April 1994 and March 1995. It has been determined that these equations which express the 99th percentile of the incident solar radiation, have a -9% deviation from our measured values.
Keywords: Atmospheric humidity; Estimation; Mathematical models; Meteorology; Regression analysis; Soils; Temperature; Geographical data; Meteorological data; Monthly mean global solar radiation; Multiple linear regression; Predicted solar radiation; Sine of declination angle; Solar radiation